Distribución geográfica de Spodoptera frugiperda (Smith) en Ecuador y su relación con parámetros climáticos. - López Quispe, Pablo Gonzalo (2021)
Corn (Zea mays L.) is cultivated due to its great adaptability in the different agroclimatic zones in Ecuador and its high genetic potential for yield, however, the incidence of a series of pests, diseases and weeds in the different agro-systems that cause production losses of up to 48.5%, Spodoptera frugiperda being one of the most economically important pests. The lack of updated information on the population dynamics and areas of incidence of this pest and its relationship with climatic parameters represent a more complicated scenario. The present study aimed to determine the geographical distribution of S. frugiperda in Ecuador in relation to the favorable climatic parameters in the appearance, incidence and severity in different producing areas in the Sierra, Costa and Oriente regions. Significant differences were detected in the percentage of incidence and severity in the sampling locations, being higher in the province of El Oro (50.7%) in the Costa region, followed by Orellana (45%) in the Oriente region, while In the provinces of the Sierra region, the percentages were relatively low in Tungurahua, Loja and Bolívar with 15%, 13% and 10%, respectively. A positive correlation was also found between the climatic parameters evaluated and the incidence and severity of the plague in the corn crop in the provinces of the Costa area, obtaining the following equations y = 12.685 + 0.7041x for severity (p < 0.01; R2 = 0.8941) and y = 7.1347 + 0.3963x (p <0.01; R2 = 0.8443) for incidence. A distribution map of S. frugiperda in our country is presented.